2012
DOI: 10.1371/journal.pone.0046794
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cerebral Autoregulation Is Associated with Brain Atrophy and Worse Functional Status in Chronic Ischemic Stroke

Abstract: Dynamic cerebral autoregulation (dCA) is impaired following stroke. However, the relationship between dCA, brain atrophy, and functional outcomes following stroke remains unclear. In this study, we aimed to determine whether impairment of dCA is associated with atrophy in specific regions or globally, thereby affecting daily functions in stroke patients.We performed a retrospective analysis of 33 subjects with chronic infarctions in the middle cerebral artery territory, and 109 age-matched non-stroke subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 59 publications
0
49
0
Order By: Relevance
“…For example, systemic circulatory or autonomic dysfunction-induced attenuation in ECA regulation may exacerbate intracranial cerebral blood flow regulation. This has important clinical implications given that impaired CA is associated with poor clinical outcome, e.g., brain atrophy and cognitive dysfunction, following ischemic stroke and brain injury, and may also predispose to neurodegenerative disease (2,3). Collectively, the present findings provide mechanistic insight into how impaired systemic circulatory and autonomic function can translate into regional brain disease.…”
Section: Perspectives and Significancementioning
confidence: 62%
“…For example, systemic circulatory or autonomic dysfunction-induced attenuation in ECA regulation may exacerbate intracranial cerebral blood flow regulation. This has important clinical implications given that impaired CA is associated with poor clinical outcome, e.g., brain atrophy and cognitive dysfunction, following ischemic stroke and brain injury, and may also predispose to neurodegenerative disease (2,3). Collectively, the present findings provide mechanistic insight into how impaired systemic circulatory and autonomic function can translate into regional brain disease.…”
Section: Perspectives and Significancementioning
confidence: 62%
“…Hypertension is linked with ischemic injury (e.g., white matter hyperintensities) that often leads to brain shrinkage. 52-55 Cerebral hypoperfusion accelerates brain atrophy in medical and neurological populations 8,56,57 and recent work demonstrates its association with cortical thickness in older adults. 30 Nevertheless, the effects of hypertension on cortical thickness was attenuated after age was entered as covariate.…”
Section: Discussionmentioning
confidence: 99%
“…One study indicated that better bilateral dynamic CA is associated with less atrophy and better long-term functional status in older adults with chronic ischaemic infarctions 3. The other showed that impairment of dynamic CA ipsilateral to acute ischaemic stroke is associated with larger infarction, and dysautoregulation tends to worsen and spread to the contralateral side over the first days poststroke and is associated with poor clinical outcome 4.…”
Section: Clinical Applications Of Ca Studies In Strokementioning
confidence: 99%